Ubiquitination and Ubiquitin-Like Modifications as Mediators of Alternative Pre-mRNA Splicing in Arabidopsis thaliana - Lan, Wei; Qiu, Yuhao; Xu, Yun; Liu, Yalin; Miao, Ying (Frontiers in Plant Science, 2022)
Alternative splicing (AS) is a common post-transcriptional regulatory process in eukaryotes. AS has an irreplaceable role during plant development and in response to environmental stress as it evokes differential expression of downstream genes or splicing factors (e.g., serine/arginine-rich proteins). Numerous studies have reported that loss of AS capacity leads to defects in plant growth and development, and induction of stress-sensitive phenotypes. A role for post-translational modification (PTM) of AS components has emerged in recent years. These modifications are capable of regulating the activity, stability, localization, interaction, and folding of spliceosomal proteins in human cells and yeast, indicating that PTMs represent another layer of AS regulation. In this review, we summarize the recent reports concerning ubiquitin and ubiquitin-like modification of spliceosome components and analyze the relationship between spliceosome and the ubiquitin/26S proteasome pathway in plants. Based on the totality of the evidence presented, we further speculate on the roles of protein ubiquitination mediated AS in plant development and environmental response.